MMUNOHISTOCHEMICAL ANALYSIS OF NF-kB (P0/P) IN PATIENT WITH AGGRESSIVE AND CHRONIC PERIODONTITIS - Prahasanti, Chiquita (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: Nuclear factor-kappaB (NF-ÎºB) is a protein complex that plays a role in transcription factors and in response to inflammation. Periodontitis is a periodontal disorder caused by various bacteria such as A. actinomycetemcomitan and P.gingivalis whose LPS is closely related to NFÎºB (p50/p65). Aim: This study observed whether NF-ÎºB (p50/p65) played a role in aggressive and chronic periodontitis. Methods: Data were obtained from periodontal tissue 40 patients with aggressive periodontitis and 40 patients with chronic periodontitis. Samples were derived from periodontal tissue with abnormalities and NFÎºB (p50/p65) protein expression test was performed by immunohistochemistry. The statistical test used was the t-test. Results: In NF-ÎºB (p50) the t value was -12 041 and significance 0.000, with Î± = 5%, showing significant difference in protein expression of NF-ÎºB (p50) between patients with aggressive periodontitis and chronic periodontitis. OR estimation for the value of protein expression of NFÎºB (p50) was 0.64 (sign. = 0.000). It shows that if the protein expression of NFÎºB (p50) of the respondents is incremented by 1 (one) unit, the risk of chronic periodontitis increases 1.64 times. Box plot diagram shows that the distribution of the protein expression of NFÎºB (p50) between patients with aggressive periodontitis and chronic periodontitis patients is significantly different. In NF-ÎºB (p65) the Z value was -7.137 and significance of 0000, with Î±= 5%, showed significant differences in protein expression of NF-ÎºB (p65) between patients with aggressive periodontitis and chronic periodontitis. OR estimates for protein expression of NFÎºB (p65) was 0.66 (sign. = 0.000). This indicates that if the protein expression of NFÎºB (p65) respondents is incremented by 1 (one) unit, the risk of chronic periodontitis increases 1.5 times. Box plot diagram shows that the distribution of the protein expression of NFÎºB (p65) between patients with aggressive and chronic periodontitis patients is significantly different. Conclusion: The protein expression of NF-ÎºB (p50/p65) has more influence on the incidence of chronic periodontitis patients, so it can be used as a marker for chronic periodontitis.